Out-of-pocket payments and economic consequences from tuberculosis care in eastern China: income inequality - Yan Liu; Cai-Hong Xu; Xiao-Mo Wang; Zhen-Yu Wang; Yan-Hong Wang; Hui Zhang; Li Wang (BMC, 2020)
Abstract Background Despite the availability of free tuberculosis (TB) diagnosis and treatment, TB care still generates substantial costs that push people into poverty. We investigated out-of-pocket (OOP) payments for TB care and assessed the resulting economic burden and economic consequences for those with varying levels of household income in eastern China. Methods A cross-sectional study was conducted among TB patients in the national TB programme networks in eastern China. TB-related direct OOP costs, time loss, and coping strategies were investigated across households in different economic strata. Analysis of Variance was used to examine the differences in various costs, and Kruskal-Wallis tests were used to compare the difference in total costs as a percentage of annual household income. Results Among 435 patients, the mean OOP total costs of TB care were USD 2389.5. In the lower-income quartile, OOP payments were lower, but costs as a percentage of reported annual household income were higher. Medical costs and costs prior to treatment accounted for 66.4 and 48.9% of the total costs, respectively. The lower the household income was, the higher the proportion of medical costs to total costs before TB treatment, but the lower the proportion of medical costs patients spent in the intensive phase. TB care caused 25.8% of TB-affected households to fall below the poverty line and caused the poverty gap (PG) to increase by United States Dollar (USD) 145.6. Patients in the poorest households had the highest poverty headcount ratio (70.2%) and PG (USD 236.1), but those in moderately poor households had the largest increase in the poverty headcount ratio (36.2%) and PG (USD 177.8) due to TB care. Patients from poor households were more likely to borrow money to cope with the costs of TB care; however, there were fewer social consequences, except for food insecurity, in poor households. Conclusions Medical and pretreatment costs lead to high costs of TB care, especially among patients from the poorest households. It is necessary to train health system staff in general hospitals to promptly identify and refer TB patients. Pro-poor programmes are also needed to protect TB patients from the medical poverty trap.